Combined effect of inlet pressure, total cycle energy, and start of injection on low load reactivity controlled compression ignition combustion and emission characteristics in a multi-cylinder heavy-duty engine fueled with gasoline/diesel. (15th December 2018) - Han, Weiqiang; Li, Bolun; Pan, Suozhu; Lu, Yao; Li, Xin
Abstract: Reactivity controlled compression ignition (RCCI) is demonstrated as a controllable high efficiency and clean combustion strategy, which is confirmed to be affected by either inlet pressure (IP), total cycle energy (Etotal ), or start of injection (SOI). This paper discussed their combined effect on low load RCCI combustion and emission characteristics in a multi-cylinder heavy-duty engine fueled with gasoline/diesel. Results show that low temperature heat release (LTHR) only occurs when SOI is sufficiently advanced. Combustion duration (CD) is lengthened, shortened and unchanged with SOI advance under different Etotal s, while lengthened with IP increase. NOX emission first increases and then decreases with SOI advance, and declines with IP increase or Etotal decrease. Trend CO changes with SOI or IP becomes opposite at the lowest Etotal, comparing with that at relatively high Etotal s. HC emission decreases with SOI advance or Etotal increase, while it is insensitive to IP. Trend number of nuclear particle ( N u m n ) changes with IP becomes opposite at the highest Etotal, comparing with that at relatively low Etotal s, while N u m n decreases with SOI advance or Etotal increase. Both number of aggregated particle ( N u m a ) and soot first decreases and then increases with SOI advance, and decreases with Etotal decrease or IP increase. Highlights: Low temperature heat release occurs when start of injection is sufficiently advanced. Combustion duration is lengthened, shortened and unchanged under diverse conditions. Opposite trends of carbon monoxide appear under the lowest total cycle energy. Opposite trends of nuclear particle number appear under highest total cycle energy. Trends of the rest emissions changes with the three parameters remains unchanged.